2019
DOI: 10.21203/rs.2.12398/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge of Preconception Care and Associated Factors among Pregnant Mothers with Pre-existing Diabetes Mellitus in selected Governmental Hospitals, Addis Ababa Ethiopia

Abstract: Background: Many women with diabetes mellitus experience high rates of unintended pregnancies, infant morbidity and mortality and preventable birth defects.Thus, preconception care offers the potential for earlier risk assessment and intervention that can benefit women before pregnancy and ensure the healthiest possible start for the newborn child. The aim of this study is to assess the knowledge and experience of preconception care and associated factors among pregnant mothers with pre-existing diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 5 publications
(5 reference statements)
4
16
0
Order By: Relevance
“…Women who had formal education were nearly two times more likely to have good awareness of NCDs screening during the preconception period than their counterparts. This find was consistent with previous studies from different countries [40,48,49,[51][52][53]. Attending education gives individuals the chance of gaining information directly from the class or indirectly from discussion with friends or using different information sources like novel social media.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Women who had formal education were nearly two times more likely to have good awareness of NCDs screening during the preconception period than their counterparts. This find was consistent with previous studies from different countries [40,48,49,[51][52][53]. Attending education gives individuals the chance of gaining information directly from the class or indirectly from discussion with friends or using different information sources like novel social media.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study revealed that 73.7% of the respondents had good awareness of common NCDs screening during the preconception period. This finding was comparable with the studies conducted in Nigeria (76.0%) [39] and Addis Ababa Ethiopia (72.5%) [40]. This might be due to the similarity of the study population.…”
Section: Discussionsupporting
confidence: 89%
“…Evidence advocated that inadequate antenatal, medical, and preconception care are factors affecting adverse birth outcomes among diabetic women [ 6 , 25 , 26 ]. American Diabetes Association (ADA) [ 27 ] and International Diabetic Federation (IDF) [ 28 ] sets standards of medical cares like preconception counseling and preconception care to prevent the resulting adverse birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity, previous history of macrosomia, multiparity, being post-term and inadequate antenatal, medical and preconception care are among the risk factors associated with macrosomia [10,24,25]. The complications associated with foetal macrosomia affect not only the mothers but also the newborns.…”
Section: Introductionmentioning
confidence: 99%